Analisis Fisiologis Terhadap Penderita Gangguan Berbicara Cadel pada Usia Dewasa - Audrey Tiara Rabhany; Hendra Setiawan (Peneliti.net, 2023)
This study is prompted by phoneme changes in young adults aged 20 years old. Speech disorders may impede communication between sufferers and listeners. Slurred speech or dysarthria is a speech disorder that makes it difficult for sufferers to pronounce certain words, resulting in unclear phonemes (sounds). The study aims to demonstrate speech disorders (slurred speech) and the causes of slurred speech in adults. Data collection in this study was carried out by interviews via Whatsapp using voice messages containing dialogues. The method used is a literature review and a listening method using voice messages that are described in descriptive form, as well as research results tables. Qualitative data analysis is employed by providing information and explanations. The results of this study show that speech disorders on imperfect phonemes (sounds) in adults aged 20 are caused by physiological and congenital factors that begin in infancy. The phoneme (sound) of the letter 'R' at the beginning, middle, and end is not perfect because the tongue is too short. The difference in position influences the phoneme's imperfection. This study obtained 8 sound transition data, 2 sound omission data, and 16 muffled sound data.